Ginger Stimulates Hematopoiesis via Bmp Pathway in Zebrafish - Ferri-Lagneau, Karine F.; Moshal, Karni S.; Grimes, Matthew; Zahora, Braden; Lv, Lishuang; Sang, Shengmin; Leung, TinChung (PLOS ONE, 2012)
Background Anemia is a hematologic disorder with decreased number of erythrocytes. Erythropoiesis, the process by which red blood cells differentiate, are conserved in humans, mice and zebrafish. The only known agents available to treat pathological anemia are erythropoietin and its biologic derivatives. However, erythropoietin therapy elicits unwanted side-effects, high cost and intravenous or subcutaneous injection, warranting the development of a more cost effective and non-peptide alternative. Ginger (Zingiber officinale) has been widely used in traditional medicine; however, to date there is no scientific research documenting the potential of ginger to stimulate hematopoiesis. Methodology/Principal Findings Here, we utilized gata1:dsRed transgenic zebrafish embryos to investigate the effect of ginger extract on hematopoiesis in vivo and we identified its bioactive component, 10-gingerol. We confirmed that ginger and 10-gingerol promote the expression of gata1 in erythroid cells and increase the expression of hematopoietic progenitor markers cmyb and scl. We also demonstrated that ginger and 10-gingerol can promote the hematopoietic recovery from acute hemolytic anemia in zebrafish, by quantifying the number of circulating erythroid cells in the dorsal aorta using video microscopy. We found that ginger and 10-gingerol treatment during gastrulation results in an increase of bmp2b and bmp7a expression, and their downstream effectors, gata2 and eve1. At later stages ginger and 10-gingerol can induce bmp2b/7a, cmyb, scl and lmo2 expression in the caudal hematopoietic tissue area. We further confirmed that Bmp/Smad pathway mediates this hematopoiesis promoting effect of ginger by using the Bmp-activated Bmp type I receptor kinase inhibitors dorsomorphin, LND193189 and DMH1. Conclusions/Significance Our study provides a strong foundation to further evaluate the molecular mechanism of ginger and its bioactive components during hematopoiesis and to investigate their effects in adults. Our results will provide the basis for future research into the effect of ginger during mammalian hematopoiesis to develop novel erythropoiesis promoting agents.